Mappings on Fuzzy Soft Classes - Athar Kharal; B. Ahmad (Advances in Fuzzy Systems)
We define the concept of a mapping on classes of fuzzy soft sets and study the properties of fuzzy soft images and fuzzy soft inverse images of fuzzy soft sets, and support them with examples and counterexamples.